(untitled) (Hekima Review, 2010)
While the international human rights are gaining a worldwide recognition in practice, theoretically, their universality is not solidly secured. Because of their Western historical origin, some scholars see them as a cultural product which should not be imported, let alone imposed to other cultures. Yet, other scholars find in the Universal Declaration of Human Rights the embodiment of human rights found in different cultures. How, then, to reconcile the importance of cultures and the universality of human rights? This paper suggests a dialogic encounter between international human rights and cultures as a way of rethinking their universality.